Integrated geophysical and geological analysis for peripheral exploration of Makeng-type Fe-polymetallic deposits: a case study from the Dapai Fe-polymetallic deposit, SE China - Hu, Jiaxiu; Yuan, Yuan; Wu, Shaojiang; Zhang, Xinming; Hu, Bojie (Frontiers in Earth Science, 2025)
The Makeng-type Fe–polymetallic deposits in the southwestern Fujian constitute one of the most economically significant iron-polymetallic metallogenic belts of southeastern China. The Dapai iron–polymetallic deposit in Yongding County is an representative example of the Makeng-type iron–polymetallic deposits. With the progress in mining and exploration, the priority has transferred to deep and peripheral orebodies. However, the lack of high-precision ground magnetic survey, especially for the surrounding area of the Dapai deposit, constrains our understanding of its prospecting potential and further exploration orientation. Based on previous studies and an analysis of ore-controlling factors, in this study, we performed a high-precision magnetic ground survey in the Dapai deposit’s surrounding area. The reduction to the pole, upward continuation, total horizontal derivatives and magnetization vector inversion with an unstructured tetrahedral mesh were conducted on the magnetic anomaly results. The structure framework and favorable prospecting area were consequently inferred. Both of the resulting anomalies and three-dimensional inversion showed a trend extending northwards. The results were verified by borehole, revealing multi-layer ore bodies and ore-related intrusions with strong alteration below. The magnetic anomaly features, ore-controlling characteristics, and drilling results indicated that there is potential for prospecting in deeper and more peripheral positions. Based on geological and geophysical characteristics, we proposed a comprehensive prospecting model and summarized an exploration method for the Dapai iron–polymetallic deposit, which enables prospecting the deeper and surrounding areas of the Dapai deposit and provides a basis for investigations of similar Makeng-type iron–polymetallic deposits in this area.